Just Vibrations: The Purpose of Sounding Good - Cheng, William (University of Michigan Press, 2016)
Modern academic criticism bursts with what Eve Kosofsky Sedgwick once termed paranoid readings-interpretative feats that aim to prove a point, persuade an audience, and subtly denigrate anyone who disagrees. Driven by strategies of negation and suspicion, such rhetoric tends to drown out softer-spoken reparative efforts, which forego forceful argument in favor of ruminations on pleasure, love, sentiment, reform, care, and accessibility. Just Vibrations: The Purpose of Sounding Good calls for a time-out in our serious games of critical exchange. Charting the divergent paths of paranoid and reparative affects through illness narratives, academic work, queer life, noise pollution, sonic torture, and other touchy subjects, William Cheng exposes a host of stubborn norms in our daily orientations toward scholarship, self, and sound. How we choose to think about the perpetration and tolerance of critical and acoustic offenses may ultimately lead us down avenues of ethical ruin-or, if we choose, repair. With recourse to experimental rhetoric, interdisciplinary discretion, and the playful wisdoms of childhood, Cheng contends that reparative attitudes toward music and musicology can serve as barometers of better worlds.